2022
DOI: 10.1007/s10151-022-02600-5
|View full text |Cite
|
Sign up to set email alerts
|

Polidocanol foam sclerotherapy in the treatment of hemorrhoidal disease in patients with bleeding disorders: a multicenter, prospective, cohort study

Abstract: Background The management of hemorrhoidal disease (HD) in patients with bleeding disorders (BD) is challenging. Polidocanol foam sclerotherapy (PFS) is associated with a low rate of bleeding complications. The aim of this study was to compare the efficacy and safety of PFS in the treatment of HD in patients with and without BD. Methods This prospective, multicenter, cohort study enrolled patients with (group B) and without (group A) BD, with symptomatic internal HD grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 48 publications
(76 reference statements)
0
18
0
Order By: Relevance
“…The use of 3% polidocanol foam allowed a consistent reduction of local and systemic complications in comparison with previous sclerosing agents used in the past [21]. In fact, apart from one episode of acute prostatitis, described by Moser et al [10], and some of external thrombosis [7,9], there were no major complications or adverse events [6‐12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of 3% polidocanol foam allowed a consistent reduction of local and systemic complications in comparison with previous sclerosing agents used in the past [21]. In fact, apart from one episode of acute prostatitis, described by Moser et al [10], and some of external thrombosis [7,9], there were no major complications or adverse events [6‐12].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated its safety and efficacy in the last 10 years [6][7][8][9][10][11][12]. Among the main advantages that favoured its acceptance, especially during the COVID-19 pandemic where the availability of operating rooms had been reduced and elective procedures stopped or suspended [13], were the low cost, repeatability, almost total absence of complications as well as of procedural pain and discomfort for the patient even at the cost of a recurrence rate still not well defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, hemorrhoidal disease recurred in 9.4% of patients during the 12 month follow-up period. Again, this rate was no higher for patients with bleeding disorders [17].…”
mentioning
confidence: 84%
“…A recent randomized controlled trial even showed the injection of this foam to be more effective than rubber band ligation [15]. The renewed interest in this technique is well illustrated by the concomitant publication of two articles on the evaluation of polidocanol foam in this issue of Techniques in Coloproctology [16,17].…”
mentioning
confidence: 99%